Diacylglycerol kinase α‐selective inhibitors induce apoptosis and reduce viability of melanoma and several other cancer cell lines. Issue 6 (9th December 2018) - Yamaki, Atsumi; Akiyama, Rino; Murakami, Chiaki; Takao, Saki; Murakami, Yuki; Mizuno, Satoru; Takahashi, Daisuke; Kado, Sayaka; Taketomi, Akinobu; Shirai, Yasuhito; Goto, Kaoru; Sakane, Fumio
Abstract: Diacylglycerol (DG) kinase (DGK), which phosphorylates DG to generate phosphatidic acid (PA), consists of ten isozymes (α–к). Recently, we identified a novel small molecule inhibitor, CU‐3, that selectively inhibits the activity of the α isozyme. In addition, we newly obtained Compound A, which selectively and strongly inhibits type I DGKs (α, β, and γ). In the present study, we demonstrated that both CU‐3 and Compound A induced apoptosis (caspase 3/7 activity and DNA fragmentation) and viability reduction of AKI melanoma cells. Liquid chromatography‐mass spectrometry revealed that the production of 32:0‐ and 34:0‐PA species was commonly attenuated by CU‐3 and Compound A, suggesting that lower levels of these PA molecular species are involved in the apoptosis induction and viability reduction of AKI cells. We determined the effects of the DGKα inhibitors on several other cancer cell lines derived from refractory cancers. In addition to melanoma, the DGKα inhibitors enhanced caspase 3/7 activity and reduced the viability of hepatocellular carcinoma, glioblastoma, and pancreatic cancer cells, but not breast adenocarcinoma cells. Interestingly, Western blot analysis indicated that the DGKα expression levels were positively correlated with the sensitivity to the DGK inhibitors. Because both CU‐3 and Compound A induced interleukin‐2 production by T cells, it is believed that these two compounds can enhance cancer immunity. Taken together, our results suggest that DGKα inhibitors are promising anticancer drugs. Abstract : CU‐3 and Compound A induced apoptosis and viability reduction of AKI melanoma, hepatocellular carcinoma, glioblastoma, and pancreatic cancer cells. Liquid chromatography‐mass spectrometry revealed that the production of 32:0‐ and 34:0‐phosphatidic acid species was commonly attenuated by CU‐3 and Compound A. CU‐3 and Compound A can be ideal anticancer drug candidates that attenuate cancer cell proliferation and simultaneously enhance immune responses including anticancer immunity.